Effects of Mdivi-1 on Neural Mitochondrial Dysfunction and Mitochondria-Mediated Apoptosis in Ischemia-Reperfusion Injury After Stroke: A Systematic Review of Preclinical Studies - Nhu, Nguyen Thanh; Li, Qing; Liu, Yijie; Xu, Jian; Xiao, Shu-Yun; Lee, Shin-Da (Frontiers in Molecular Neuroscience, 2021)
This systematic review sought to determine the effects of Mitochondrial division inhibitor-1 (Mdivi-1) on neural mitochondrial dysfunction and neural mitochondria-mediated apoptosis in ischemia/reperfusion (I/R) injury after ischemic stroke. Pubmed, Web of Science, and EMBASE databases were searched through July 2021. The studies published in English language that mentioned the effects of Mdivi-1 on neural mitochondrial dysfunction and neural mitochondria-mediated apoptosis in I/R-induced brain injury were included. The CAMARADES checklist (for in vivo studies) and the TOXRTOOL checklist (for in vitro studies) were used for study quality evaluation. Twelve studies were included (median CAMARADES score = 6; TOXRTOOL scores ranging from 16-18). All studies investigated neural mitochondrial functions, providing that Mdivi-1 attenuated the mitochondrial membrane potential dissipation, ATP depletion, and complexes I-V abnormalities; enhanced mitochondrial biogenesis, as well as inactivated mitochondrial fission and mitophagy in I/R-induced brain injury. Ten studies analyzed neural mitochondria-mediated apoptosis, showing that Mdivi-1 decreased the levels of mitochondria-mediated proapoptotic factors (AIF, Bax, cytochrome c, caspase-9, and caspase-3) and enhanced the level of antiapoptotic factor (Bcl-2) against I/R-induced brain injury. The findings suggest that Mdivi-1 can protect neural mitochondrial functions, thereby attenuating neural mitochondria-mediated apoptosis in I/R-induced brain injury. Our review supports Mdivi-1 as a potential therapeutic compound to reduce brain damage in ischemic stroke (PROSPERO protocol registration ID: CRD42020205808).